Incorporation of Polymers into Calcined Clays as Improved Thermal Insulating Materials for Construction - Serina Ng; Bjørn Petter Jelle (Advances in Materials Science and Engineering)
Calcined clay is a Type Q supplementary cementing material according to EN197-1:2000. It possesses lower thermal conductivity than cement. To further improve its thermal insulation property, polymer-calcined clay complexes (PCCs) were produced in a one-pot synthesis. Two contrasting polymers, polystyrene (PS) and polyethylene glycol (PEG), were employed. The hydrophilicity of the polymers influenced the thermal conductivity of PCC. Hydrophilic PEG entrapped more water molecules on clay layers than the hydrophobic PS, making PEG-PCC more thermally conducting than PS-PCC. Contaminants in calcined clays played a role in affecting the overall thermal conductivity. PCC can improve thermal insulation properties for future construction applications.